Promoting health and well-being – Tools for designing community health centres and healthy neighbourhoods - Nicoletta Setola; Sabrina Borgianni (Agathón)
Within the field of studies on the built environment as a determinant of health and in the context of the ‘urban health’ approach, this article illustrates the methodology used in the Quartieri Sani Hub (lit. Healthy Neighbourhoods Hub) research to develop decision-support tools for Public Administrations and designers in the creation of healthy neighbourhoods that promote well-being. These tools include design scenarios applied to two real contexts in Florence and technical guidelines of a meta-design nature. The presented methodology highlights a recursive process between architectural design and the development of operational meta-design tools based on data derived from a participatory and analytical process developed during the research.